Digital subtraction angiography of glomus tympanicum and jugulare tumors. - Carmody, R F; Seeger, J F; Horsley, W W; Smith, J R; Miller, R W (American Journal of Neuroradiology, 1983)
Radiologic procedures used to evaluate patients with suspected glomus tumor have included plain skull radiography, temporal bone tomography, computed tomography, and cerebral angiography. Of these, only angiography has proven reliable as a screening procedure for small glomus tympanicum and jugulare tumors. Digital subtraction angiography was used as the initial examination for suspected paraganglioma in 14 patients. Intravenous digital subtraction angiography proved to be an acceptable screening tool for these highly vascular tumors. Also, intraarterial digital subtraction angiography proved very satisfactory for mapping of tumor blood supply, which greatly simplified preoperative embolization. Effectiveness of therapy was readily ascertained by serial follow-up intravenous digital subtraction angiography.